Circulating tumor DNA detection is correlated to histologic types in patients with early-stage non-small-cell lung cancer. (August 2019) - Zhang, Bin; Niu, Xueliang; Zhang, Qiang; Wang, Chunli; Liu, Bo; Yue, Dongsheng; Li, Chenguang; Giaccone, Giuseppe; Li, Shiyong; Gao, Liuwei; Zhang, Hua; Wang, Jian; et al.
Highlights: In early-stage NSCLC, tissue- pre-op plasma concordant ctDNA mutation detection ratio was higher in LUSC than in LUAD. A LUSC-LUAD classification model was built using LASSO based on ctDNA profiling. tDNA-ctDNA concordant ratio was associated with gene mutations, histology subtype and tumor size in early-stage NSCLC. Abstract: Objectives: Circulating tumor DNA (ctDNA) testing in plasma in patients with non-small-cell lung cancer (NSCLC) has the potential to be a supplemental or surrogate tool for tissue biopsy. Detection of genomic abnormalities in ctDNA and their association with clinical characteristics in early-stage NSCLC need to be clarified. Materials and methods: Here, we comprehensively analyzed gene variations of 48 tumor tissues and 48 matched preoperative (pre-op) plasma and 25 postoperative (post-op) plasma from early-stage NSCLC patients using a targeted 546 genes capture-based next generation sequencing (NGS) assay. Results: In early-stage NSCLC, the average mutation allele frequency (MAF) in pre-op plasma ctDNA was lower than that in tissue DNA (tDNA). The concordant gene variations between pre-op ctDNA and tDNA were difficult to detect. However, we found the tissue- pre-op plasma concordant ctDNA mutation detection ratio in lung squamous cell carcinoma (LUSC) was much higher than that in lung adenocarcinoma (LUAD). We also established a LUSC-LUAD classification model by a least absolute shrinkage and selection operator (LASSO) based approach to help separate LUAD from LUSC based on ctDNA profiling. This model included 14 gene mutations and extracted an accuracy of 89.2% in the training set and 91.5% in the testing set. Correlation analysis showed tDNA-ctDNA concordant ratio was related to histologic subtype, gene mutations and tumor size in early-stage NSCLC. Conclusion: This study suggests histology subtype and gene mutations could affect ctDNA detection in early-stage NSCLC. NGS-based ctDNA profile has the potential utility in LUSC-LUAD classification.